Mafic High‐Pressure Rocks Are Preferentially Exhumed From Warm Subduction Settings - Peter E. vanKeken; Ikuko Wada; Geoffrey A. Abers; Bradley R. Hacker; Kelin Wang (Geochemistry, Geophysics, Geosystems, 2018)
Abstract The oceanic crust that enters a subduction zone is generally recycled to great depth. In rare and punctuated episodes, however, blueschists and eclogites derived from subducted oceanic crust are exhumed. Compilations of the maximum pressure‐temperature conditions in exhumed rocks indicate significantly warmer conditions than those predicted by thermal models. This could be due to preferential exhumation of rocks from hotter conditions that promote greater fluid productivity, mobility, and buoyancy. Alternatively, the models might underestimate the forearc temperatures by neglecting certain heat sources. We compare two sets of global subduction zone thermal models to the rock record. We find that the addition of reasonable amounts of shear heating leads to less than 50 °C heating of the oceanic crust compared to models that exclude this heat source. Models for young oceanic lithosphere tend to agree well with the rock record. We test the hypothesis that certain heat sources may be missing in the models by constructing a global set of models that have high arbitrary heat sources in the forearc. Models that satisfy the rock record in this manner, however, fail to satisfy independent geophysical and geochemical observations. These combined tests show that the average exhumed mafic rock record is systematically warmer than the average thermal structure of mature modern subduction zones. We infer that typical blueschists and eclogites were exhumed preferentially under relatively warm conditions that occurred due to the subduction of young oceanic lithosphere or during the warmer initial stages of subduction.